The clinical and immunological features of pediatric COVID-19 patients in China - Chen, Juan; Zhang, Zhen-Zhen; Chen, Yao-Kai; Long, Quan-Xin; Tian, Wen-Guang; Deng, Hai-Jun; Hu, Jie-Li; Zhang, Xian-Xiang; Pu-Liao; Xiang, Jiang-Lin; Wang, Dao-Xin; Hu, Peng; et al. (Genes & diseases, 2020)
In December 2019, the corona virus disease 2019 (COVID-19) caused by novel coronavirus (SARS-CoV-2) emerged in Wuhan, China and rapidly spread worldwide. Few information on clinical features and immunological profile of COVID-19 in paediatrics. The clinical features and treatment outcomes of twelve paediatric patients confirmed as COVID-19 were analyzed. The immunological features of children patients was investigated and compared with twenty adult patients. The median age was 14.5-years (range from 0.64 to 17), and six of the patients were male. The average incubation period was 8 days. Clinically, cough (9/12, 75%) and fever (7/12, 58.3%) were the most common symptoms. Four patients (33.3%) had diarrhea during the disease. As to the immune profile, children had higher amount of total T cell, CD8+ T cell and B cell but lower CRP levels than adults (P < 0.05). Ground-glass opacity (GGO) and local patchy shadowing were the typical radiological findings on chest CT scan. All patients received antiviral and symptomatic treatment and the symptom relieved in 3–4 days after admitted to hospital. The paediatric patients showed mild symptom but with longer incubation period. Children infected with SARS-CoV-2 had different immune profile with higher T cell amount and low inflammatory factors level, which might ascribed to the mild clinical symptom. We advise that nucleic acid test or examination of serum IgM/IgG antibodies against SARS-CoV-2 should be taken for children with exposure history regardless of clinical symptom.